INVESTIGATION OF TOXIGENICITY OF CLOSTRIDIUM DIFFICILE BY CELL CULTURE METHOD - M.H. Salari (Tehran University of Medical Sciences, 1997)
Clostridium diffcile is part of the normal intestinal flora in a small proportion of healthy persons. When exposed to antibiotics, the normal enteric flora is altered, permitting the overgrowth of these relatively resistant organisms. Proliferation of the organisms with localized production of their toxins leads to disease (pseudomembran colitis or antibiotic associated diarrhea). In this study, by anaerobic and Hela cell culture method, toxigenicity of 132 Clostridium difficile strains, isolated from 2517 enterocolitis patients' specimens, were investigated and the results were obtained as very high toxigenic in 21 cases (15.9%), high toxingenic in 17 cases (12.8%), moderate toxigenic in 18 cases 13.6%, low toxigenic in 12 cases (9%) and nontoxigenic in 64 case (48%).